Hybrid Working and Its Impact on Work Effectiveness & Student Learning Outcomes - Feby Arma Putra; Elmi Nurvianti (Journal of Science and Education (JSE), 2025)
The development of digital technology and changes in work patterns due to the COVID-19 pandemic have prompted various higher education institutions to implement hybrid work and learning systems. Hybrid working is a combination of online and offline work and learning that is flexible, efficient, and adaptive. This study aims to analyze the effect of hybrid working on the work effectiveness of educational staff (tendik) and student learning outcomes. Additionally, the DeLone and McLean model is used to measure the success of hybrid working implementation through six main variables: system quality, information quality, service quality, use, user satisfaction, and net benefit. The study involved 150 respondents, including educational staff and third-year students at PGRI Banten Polytechnic. Data was collected via an online questionnaire using Google Forms. Analysis was conducted using validity and reliability tests via SPSS 22, followed by structural equation modeling (SEM) to test the relationships between variables in the model. The analysis results indicate that the hybrid system has a significant impact on the work effectiveness of educational staff and student learning outcomes. System quality and information quality are the dominant indicators influencing user satisfaction and net benefit from the hybrid system. Furthermore, a SWOT analysis was conducted to formulate strategies for strengthening the implementation of hybrid working in higher education institutions. Effective strategies include improving digital literacy, utilizing more stable technology, and strengthening communication and monitoring based on digital platforms. The DeLone and McLean model has proven to be a reliable measurement tool for evaluating the success of hybrid work systems and providing direction for sustainable development strategies. With these findings, educational institutions are expected to be more prudent in designing hybrid working policies that are not only efficient but also have a positive impact on all stakeholders.